Sofinare-workflow management, a case study: a web database application development - Martins, José Daniel Posada Vilas Boas (2012)
A web-based application has been developed to ensure recording of all details of maintenance works carried out at SOFINARE (a Portuguese aeronautical company meeting EASA PART 145 standards). The main objective is to have a safe and easy-to-use system to control and retain maintenance work records. This application is just the beginning of a future software that later will be developed by Grupo7Air engineers to be used in their organisation covering specific aspects such as having all maintenance information (aircrafts, technicians, manuals, maintenance programmes, works, inventory, component tracking, etc.) stored in a vast group of tables, which will form the database, in a way that, any data one wants to know can be picked up in those tables through the Software. This research was carried out at AEROTÉCNICA and SOFINARE, both Portuguese aeronautical organisations, with the purpose of analysing the maintenance process and also to study how a software implementation can be done to controlling the maintenance process in the aeronautical maintenance industry. Later on, this software can be continuously developed and upgraded to be widely used in the entire Grupo7Air organisation, to help through the maintenance management while complying with the existent aeronautical legislation requirements, while ensuring aircraft maintenance planning is efficient and accurate, and, at the same time, helping the needs of the company to survive, that is, being able to keep making money in the present crisis. This work begun by planning how the database should be created in order to save maintenance organisation data safely and correctly, so it can be used later to future software tasks. This application has been developed (and it will continue to be) using PHP open source language and MySQL database resource. The use of PHP and MySQL as the developing programming languages allow this software to be a multiple platform software in a time saving way, since the source code is recognized by the different browsers, that is, it works on Internet Explorer, or Mozilla Firefox for example, being these, the favorite browsers of the company’s staff, running under Windows, OS X or Linux. Implementing and learning the software through one’s favorite browser is thus simplified, it doesn’t have to be installed in each employee PC and also reduces implementation costs. The PC has only to be able to connect to the internal server and have access to internal database where all data are safely stored through this application.